Building Pastoralist Resilience to Shocks and Disaster Risks: VSF Germany Experiences - Bekele, Abay (Vtrinaires Sans Frontires Germany, 2025)
Presented at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025